2011
DOI: 10.1007/978-3-642-21210-9_30
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Component Fault Trees into the UML

Abstract: Abstract. Efficient safety analyses of complex software intensive embedded systems are still a challenging task. This article illustrates how model-driven development principles can be used in safety engineering to reduce cost and effort. To this end, the article shows how well accepted safety engineering approaches can be shifted to the level of model-driven development by integrating safety models into functional development models. Namely, we illustrate how UML profiles, model transformations, and technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…But not always one component has only one function, the implementation from one function can be executed by more than a component or more than one function may be assigned to a component [25,26]. Approaches like, for example, the extension from FTA including the functional dependency [27,28] show that reconsideration is necessary for the benefit of the functional orientation. Liggesmeyer [20] considers for applying FTA and FMEA by his modularized model the system and system environment, though the analysis to focus only on components and functions that are not taken into account.…”
Section: Analysis Of Methodsmentioning
confidence: 99%
“…But not always one component has only one function, the implementation from one function can be executed by more than a component or more than one function may be assigned to a component [25,26]. Approaches like, for example, the extension from FTA including the functional dependency [27,28] show that reconsideration is necessary for the benefit of the functional orientation. Liggesmeyer [20] considers for applying FTA and FMEA by his modularized model the system and system environment, though the analysis to focus only on components and functions that are not taken into account.…”
Section: Analysis Of Methodsmentioning
confidence: 99%
“…Popular approaches (Adler, Domis, Höfig, Kemmann, Kuhn, Schwinn, and Trapp 2011) and (David, Idasiak, and Kratz 2009) have shown that UML as modeling language can be efficiently used with analysis and verification methods such as FMEA (failure mode and effect analysis), fault tree analysis (FTA), design walk through (Gvero, 2013), code-generation and many more. The drawback of UML, in terms of simulation to verify the system behavior is, that code-generation can only be done at a very late stage or even at the end of the design process, when all details are very well known.…”
Section: Related Workmentioning
confidence: 99%
“…With the aim of modularizing fault trees, Component Fault Trees (CFTs) [2] were introduced. In [3], [4], and [5], Component Integrated Fault Trees (C 2 FT) extended this modularization concept and presented the means to Communicated by Federico Ciccozzi, Antonio Cicchetti and Andreas Wortmann. example use case in Chapter 5.…”
Section: Introductionmentioning
confidence: 99%